The Impact of Implementing E-Government Systems, Information Technology, and Task Suitability on Employee Performance at the Department of Communication and Information of Badung Regency - Gede Semarajana; Ni Putu Tirka Widanti; I Made Kartika (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
One important step to improve employee performance is to pay attention to the factors that influence it, namely electronic-based government systems (e-government), information technology and task suitability. Based on this, the problem that can be formulated in this research is what is the partial and simultaneous influence of the implementation of an electronic-based government system (e-government), information technology and task suitability on employee performance at the Badung Regency Communication and Information Service. Data collection in this research was carried out by means of documentation, observation, interviews and questionnaires with 46 employees. The collected questionnaires were then analyzed using multiple linear regression analysis. Based on calculations, it was found that the results of implementing an electronic-based government system (E-Government) had a positive and significant effect on employee performance at the Badung Regency Communication and Information Service. Information technology has a positive and significant effect on employee performance at the Badung Regency Communication and Information Service. Task suitability has a positive and significant effect on employee performance at the Badung Regency Communication and Information Service. The implementation of electronic-based government systems (E-Government), information technology and task suitability simultaneously have a positive and significant effect on employee performance at the Badung Regency Communication and Information Service.